An anionic sod-type terbium-MOF with extra-large cavities for effective anthocyanin extraction and methyl viologen detection. Issue 47 (23rd May 2018) - Du, Wei; Zhu, Zhifeng; Bai, Yue-Ling; Yang, Zhen; Zhu, Shourong; Xu, Jiaqiang; Xie, Zhaoxiong; Fang, Jianhui
Abstract : An anionic sod -type zeolitic MOF with extra-large cavities has been synthesized through a 4 + 6 strategy, which can efficiently extract natural product anthocyanins from blackberries and rapidly release them into NaCl aqueous solution. Abstract : An anionic sod -type zeolitic metal–organic framework [(CH3 )2 NH2 ]9 Tb6 (η 6 -TATAT)4 (H2 O)12 ·3Cl·DMA·7H2 O [1, H6 TATAT = 5, 5′, 5′′-(1, 3, 5-triazine-2, 4, 6-triyltriimino)tri-1, 3-benzenedicarboxylic acid] has been synthesized by metal–ligand directed assembly of hexacarboxylic acid units and Tb 3+ ions. Compound1 with extra-large cavities can efficiently extract natural product anthocyanins from blackberries and release them rapidly into NaCl aqueous solution. And, the nature of the anionic framework makes it very sensitive to detect cationic methyl viologen (MV 2+ ) with a detection limit as low as 1 × 10 −8 M.